A familial 7q36.3 duplication associated with agenesis of the corpus callosum. (5th May 2015) - Wong, Keith; Moldrich, Randal; Hunter, Matthew; Edwards, Matthew; Finlay, David; O'Donnell, Sheridan; MacDougall, Tom; Bain, Nicole; Kamien, Benjamin
<x xml:space="preserve">Abstract</x> Small chromosomal duplications involving 7q36.3 have rarely been reported. This clinical report describes four individuals from a three‐generation family with agenesis of the corpus callosum (ACC) and a 0.73 Mb duplication of 7q36.3 detected by array CGH. The 7q36.3 duplication involves two genes: RNA Binding Motif Protein 33 (RBM33) and Sonic Hedgehog (SHH). Most affected family members had mild intellectual disability or borderline intellectual functioning, macrocephaly, a broad forehead, and widely spaced eyes. Two individuals had a Chiari type I malformation. This is the first family reported with ACC associated with a small duplication of these genes. While we cannot establish causation for the relationship between any single gene and the ACC in this family, there is a role for SHH in the formation of the corpus callosum through correct patterning and assembly of the commissural plate, and these data concur with vertebrate studies showing that a gain of SHH expands the facial primordium. © 2015 Wiley Periodicals, Inc.